Вы находитесь на странице: 1из 0

..

1
1.1.
1.2.
1.3.
1.4.
1.5.
1.6.
1.7.
1.8.
1.9.
1.10.
2

2.1.
2.2.
2.3.
2.4.
2.5.
2.6.
2.6.1.
2.6.2.
2.7.
2.7.1.
2.7.2.
2.7.3.

2
2
3
6
9
10
11
13
16
18
19

20
21
30
32
34
37
39
39
40
43
43
44
46

1

1.1.
,
, :
, ,
,
.
,
P1 , P2 ,... (. 1,).
. ,
A B m - m ,
O .
,
m - m
. , ..
, , .
dA O m - m
n , B.
O dP
dM .
,
, dP dA = s(A) n ,
m - m O
. dP
.
dP
n , ,
n
.

. 1.
, O
() , ,

n (O ) .
, O
.
,
.
, O
, - 1n , 2 n , 3n .
,
(.1,). 9 ( 3
) ,
.
,
, . 2.

s11 s12
s
21 s 22
s 31 s 32

s13
s 23 .
s 33

,
. 2.

.
s11 , s 22 , s 33 ; s12 , s32 , s13 ,... , t11 , t 22 , t33 ,.
1.2.
. V ,
P ,
V * . P P*.
- R r,

PP * = OP * - OP .

u = r -R,
u - u1 , u 2 , u 3 .
,

. ,
,
ui = xi - X i , i = 1, 2,3 .

Q,

P,
P.

du.
u(r + dr ) = u(r ) + du ,
r + dr - - (
. 3
), Q*,


Q.

(1)
ui (r + dr ) = ui (r ) + dui .
du .
u(r + dr )
u(r )
:

ui (r + dr ) ui (r ) +

k =1

ui
u
dxk ui (r ) + i dxk ,
xk
xk

(2)


:
ui xk << 1
(1) (2),
u
dui = i dxk = Aik dxk ,
xk
Aik - Q
P
:
1
1
Aik = ( Aik + Aki ) + ( Aik - Aki ) =
2
2
= e ik + jik ,

1
1 u u
eik = ( Aik + Aki ) = i + k (3)
2
2 xk xi
,
eik = e ki ;

1
( Aik - Aki ) = 1 ui - uk 2 xk xi
2

jik = - jki .
X 1 = x, X 2 = y , X 3 = z

e11 e12 e13
(4)
e = e 21 e 22 e 23

e 31 e 32 e 33
(. 4).
jik =

z
e zz

g xz
x

e xx

. 4.
()
. ,
Ddx
Ddz
e xx
, e zz
.
dx
dz


g xz = g zx = 2e zx .
, (3)
u y
u
u
e xx = x , e yy =
, e zz = z ,
x
y
z
u y
u y
u
u
2e xy = 2e yx = x +
= g xy , 2e yz = 2e zy = z +
= g yz , (5)
y
y
x
z
u x u z
2e zx= 2e xz=
+ = g zx ,
z
x
u x , u y , u z -
.
e kk = e11 + e 22 + e 33
. dx10 , dx20 , dx30 - .

V 0 = dx10 dx20 dx30 .


( -) (.5)

dx1 , dx2 , dx3

Ddx3

V = dx1 x2 dx3
Ddx2

)(

)(

V = dx10 + Ddx1 x20 + Ddx2 dx30 + Ddx3 .

Ddx1

. 5.

DV = V - V 0 =
Ddx Ddx2 Ddx3
- dx10 dx 20 dx30 =
1 +
= dx10 dx20 dx30 1 + 01 1 +
0
0

dx1
dx2
dx3

= V0 [(1 + e11 )(1 + e11 )(1 + e 33 ) - 1] =

= V0 (e11 + e 22 + e 33 + e11e 22 + e 22 e 33 + e 33e11 + e11e 22 e 3 )

V - V0
e11 + e 22 + e33 = e kk ,
eij << 1
(6)
V0

.
e kk = e xx + e yy + e zz = q .
(7)
1.3.


l - l0
e=
l0
,


l - l0
s = y(e )
. 6.


s = Ee .
(8)
.
E - .
,
, . ,

( ),
,
1-2 %
,

b - b0
e =
,
b0
b0 b - .
e
( ).
, ,

s
e = -ne = -n .
(9)
E
, n .


sij = 2meij + d ij le kk .
(10)
l m - , dij - ,
1, i = j;
dij =
0, i j ,
(10) i=j:
V - V0
2

s11 + s 22 + s33 = s kk = -3 p e = 3 l + m (e11 + e 22 + e 33 ) = 3 Ke kk 3K


3
V0

K .
1
1 V
2
= - e , K = l + m
3
K
V p
(10)
2

s11 = 2me11 + le kk = 2me11 + K - m (1 - 2n )e11 = Ee11 ,


3

0 = 2me 22 + le kk = -2mne11 + K - m (1 - 2n )e11 ,


3

0 = 2me33 + le kk = -2mne11 + K - m (1 - 2n )e11 .


3


E
En
E
,m=
.
, l=
K=
2(1 + n )
(1 + n )(1 - 2n )
3(1 - 2n )
(8)
t = Gg ,

G - .
(10) , , , xz
s xz = 2me xz .
, m = G .
:
sij = Cijabe ab .

:
s11 = (l + 2m )e11 + l (e 22 + e33 ) ,
s 22 = (l + 2m )e 22 + l(e11 + e33 ) ,
s33 = (l + 2m )e33 + l (e 22 + e11 ) ,
(11)
s12 = s 21 = 2me12 ,
s 23 = s32 = 2me32 ,
s13 = s31 = 2me13 .
,
s xx = 2me xx + lq , s yy = 2me yy + lq ,
s zz = 2me zz + lq ,
(12)
t xy = 2me xy = Gg xy , t yz = 2me yz Gg yz , t zx = 2me zx Gg zx .
(3), (5) , (11)
(12) .
,
.

sij , j + rX j = 0
(13)
.

s xx t xy t xz
+
+ rX = 0 ,
+
x
z
y
t yx s yy t yz
(14)
+
+
+ rY = 0 ,
x
y
z
t zx t zy s zz
+
+
+ rZ = 0 ,
x
y
z
X , Y , Z - ,
.

2u
sij , j + rX j = r 2i - (15)
t
.

s + rF = r

2u
2

t
,

2u x
s xx t xy t xz
+ rX = r 2
+
+
z
x
y
t

t yx
x

s yy
y
t zy

t yz
z

+ rY = r

2u y
t 2
2u z

(16)

t zx
s
+
+ zz + rZ = r 2
x
y
z
t
15 (5), (12) (16)

s xx , s yy , s zz , t xy , t yz , t zx ,

e xx , e yy , e zz , e xy , e yz , e zx

ux ,u y ,uz ,
.. 15 .
15
15 ,
, .
,
. , 15
, .
1.4.
,
(.., ),
*

2 e xx
y 2
2 e yy
z 2
2 e zz
x 2

2 e yy
x 2

2 e zz

2 e xx

y 2
z 2

=2
=2

2 e xy
xy
2 e yz
yz

,
,

2 e zx
,
=2
zx

1., ; 2. ., .
, 3.,

(17)

10

e yz e zx e xy

+
z x
y
z

e zx e xy e yz

=
+
x y
z
x

2 e zz
,
xy
2 e xx
,
yz

2
e xy e yz e zx e yy

=
.
+
y z
x
y zx

, .

.


, .

1.5.

.
. ,
(12) (16).

(l + m ) q + mDu x + rX
x

=r

2u x
t 2

2u y
q
(l + m ) + mDu y + rY = r 2
y
t

(18)

q
2u z
(l + m ) + mDu z + rZ = r 2
z
t
.

r

2u
t 2

= (l + m ) u + mDu + rF .

(19)


.

(18),
(5) , , -
(12).

11

1.6.

. (16) ,

s xx , s yy , s zz , t xy , t yz , t zx .
,
.

. s kk = 3Ke kk (. 1.3),
(10)
s
s ij = 2me ij + d ij l kk
3K

1
l s kk
1
n

e ij =
s ij - d ij
=
s
s
ij
kk
.
2m
2m 3K 2G
1+ n
(17),
2
2 t xy
2 s xx s yy
n 2 s 2 s
,
+
=2
+
1 + n x 2 y 2
xy
y 2
x 2

2 s yy
z 2

2 s zz
x 2

2 s zz

2 s xx

y 2

z 2

2 t yz
n 2 s 2 s
,
=2
+
1 + n y 2 z 2
yz

2 t zx
n 2 s 2 s
=2
+
1 + n x 2 z 2
zx

t xy t yz
2 s xx
n 2s
t
= zx +
yz 1 + n yz x y
z
x
2 s yy

(20)

n 2s
t xy t yz t zx
,
=
+
zx 1 + n zx y z
x
y
2 s zz
n 2s
t yz t zx t xy
.
=
+
xy 1 + n xy z x
y
z
(),
.
.
.
(20)
(14),

12

2 s xx
y 2

2 s xx
z 2

2 s yy + s zz
x 2

)-

n 2 s 2 s 2 s
2
+
+
=
1 + n x 2 y 2 z 2

t xy
t xy
t zx
t
s
= - xx + rX .
+2
= 2 zx +
zx
xy
x z
y
x x

(21) ,
1 2s
n
X
.
Ds xx +
2
D
=
r
s
1 + n x 2 1 + n
x
(22) x , z,
1 2s
n
Y
,
D
s
=
r
Ds yy +
2
1 + n y 2 1 + n
y
=2

(21)

(22)

1 2s
n
Z
s
D
=
r
.
Ds zz +
2
1 + n z 2 1 + n
z
(22),
X Y Z
2(1 - n )
Ds = -2r
+
+
(23)
.
1+ n

(23) (22),
1 2s
X
n X Y Z
Ds xx +
=
2
r
r
+
+

.
1 + n x 2
x
1 - n x y z
(20)
, (14):
2 s xx
n 2s
t t xy t yz
= zx +
=
yz 1 + n yz y x z x x 2

=-

s yy t yz
t yz
t yz s zz

-
+
r
Z
+
+
r
Y
+
z y
x 2 =
z

z
y y

= - Dt yz -

2 s yy + s zz

) - r Z + Y .

y z
yz


Z Y
n 2s
Dt yz +
= -r
+
.
1 + n yz
y z

1 2s
X
n X Y Z
Ds xx +
=
2
r
r
+
+

,
1 + n x 2
x
1 - n x y z

Ds yy +

1 2s
Y
n X Y Z
=
2
r
r
+
+

,
1 + n y 2
y
1 - n x y z

(24)

13

Ds zz

1 2s
Z
n X Y Z
+
2
=
r
r
+
+

,
1 + n z 2
1 - n x y z
z
X Y
n 2s
Dt xy +
= -r
+
,
1 + n xy
y x

Z Y
n 2s
Dt yz +
= -r
+
,
1 + n yz
y z
n 2s
Z X
Dt zx +
= -r
+
.
1 + n zx
x z
(24) -.
, (24) .
, (23), s
. ,
.
,
(24), (14)
s xx cos(n, x ) + t xy cos(n, y ) + t xz cos(n, z ) = Pnx ,

t xy cos(n, x ) + s yy cos(n, y ) + t yz cos(n, z ) = Pny ,


t zx cos(n, x ) + t yz cos(n, y ) + s zz cos(n, z ) = Pnz .
, ,
. ,
.
1.7.

.
1. ,

(. 7), s zz ; t xz ; t yz
,
, .
s xx ; s yy ; t xy
. ,
z , .. ,
x y .

14

. 7.

. 8.

e xx
e
yx
0

e xy
e yy
0

0
0 ,
e zz

(25)

z () .


s xx t xy
+
= 0,
x
y
t yx s yy
(26)
+
= 0,
x
y

u y
u
e xx = x , e yy =
,
x
y
u yy
1 u
.
(27)
e xy = xx +
2 y
x
(. 1.6)
1
n

eij =
s
s kk ,
(28)
ij

2G
1+ n

e xx =

1
1
s xx - ns yy , e yy = s yy - ns xx ,
E
E
e xy =

(1 + n ) t
1
t xy
xy
2G
E

(29)

(27) (29)
( ,
).

15

e zz = -

n
s xx + s yy ,
E

(30)

.
.
2. ,
z .
, ,

(. 8). ,
,
. ,
.
,
,
.
,
,
, ,
u x u y x
,

y

z.

u z =0 (. 8).

u y
u x
, e yy =
,
x
y
u
1 u
e xy = x + z ,
x
2 y
e zz = 0 , e yz = 0 , e zx = 0 .

e xx =

. 9
, , ,
t xz = t yz = 0

s xx
t
yx
0

t xy
s yy
0

0
0 .
s zz


s xx , s yy t xy x y ,
s zz ( ,
) :

. .. , . 181

16

s zz = n s xx + s yy ,

e yy

[(
[(

)
)

]
]

e xy =

(1 + n ) t

1
1 - n 2 s xx - n(1 + n )s yy ,
E
1
=
1 - n 2 s yy - n(1 + n )s xx ,
E

e xx =

(31)

xy .

.
1.8.


sij = 2meij + d ij [le kk - 3Ka T (T - T0 )],
(32)
T - , , T0 , aT -
,
1 V
aT =

3V T

.
(5).
(14) (16) .
(32)

s xx = 2me xx + [lq - Kw],

s yy = 2me yy + [lq - Kw] ,


s zz = 2me zz + [lq - Kw],

(33)

t xy = 2me xy , t yz = 2me yz , t zx = 2me zx .


w = 3a T (T - T0 ) -
, (.. , ). ,
(33),
s11 + s 22 + s 33 = 3K (q - w) .
(34)
,
dq dw
=
.
dt dt

( ),

17

e
T

T
T
T
= lT
(35)
+ l T
+ l T
+ W - 3Ka T T kk ,
t x
x y
y z
z
t
l T - , ce -
, r - , ; W
.
(35)
.
, .
,
() .
,
,
.
,
, (17).
.
,
,
, ,
-.

2
2

(1 + n )Ds xx + 2s + E 1 + n Dw + w2 = 0 ,
3 1- n
x
x
2 s E 1 + n
2 w
(1 + n )Ds yy + 2 +
Dw + 2 = 0 ,
3 1- n
y
y
2 s E 1 + n
2 w
(1 + n )Ds zz + 2 +
Dw + 2 = 0
(36)
3 1- n
z
z
2
2
(1 + n )Dt xy + s + E w = 0 ,
xy 3 xy
ce r

(1 + n )Dt yz

2 s E 2w
+
+
= 0,
yz 3 yz

2 s E 2w
= 0.
+
zx 3 zx

.

, ,
- .

(1 + n )Dt zx +

18

1.9.


n

(37)
s ij = 2me ij + d ij le kk - 3K
a k (C k - C k 0 ) ,

k =1

C k - ( ) ,
n , ( C k -
), C k 0 - ; a k ,
1 V
.

ak =
3V C k
-
(5).
(14) (16) .
(37) (33),

w=3

(Ck - Ck 0 ) .

(38)

k =1


. (
) ,

C k
= - J k + wk ,
t

(39)

J k - , wk -
.

n

= 0,

k =1

=1

(40)

k =1

,

n

Jk = -

kj C k

(41)

j =1

Dkj - , , -
.

19

,
.

,
,
, .
(36),
w (38).


.

.

. (
)
.
1.10.

, , ,
, .
, s x , s y t xy
z., .. .
s z , t xz , t yz .
,
, , .

s xx , s yy t xy
, ,
.
.
,

+

Nx =

h
2

s
-

h
2

+
xx

(z )dz ,

Ny =

h
2

s
-

h
2

+
yy

(z )dz ,

N xy =

h
2

t
-

xy

(z )dz .

(42)

h
2

20

(s xx )m = N x , (s yy )m =

Ny

, (s zz )m =

Nz
.
h

(43)

(14)
.
, .

II

2.1.
1. . ,
, ..
.
,
,
(. 1).
( ) .
. ,
.
.
() ,
F
(1)
s xx = p = ,
S
S ; p = pn = F S S

, .


p 0 0
s = 0 0 0 .

0 0 0
,

. 1.
p = 2me xx + l e xx + e yy + e zz ,

(
)
0 = 2me yy + l (e xx + e yy + e zz ),
0 = 2me zz + l (e xx + e yy + e zz )

,
:
l p
n
(2)
e yy = e zz = = - p,
E
2 m 3K

21

l +m
p
p= .
3 Km
E
,

.

.


u y
u
u
p
n
n
e xx = x = , e yy =
= - p , e zz = z = - p ,
y
E
x
E
z
E
u y
u
(3)
2e xy = x +
= 0,
y
x
u
u
2e xz = x + z = 0 ,
z
x
u y u z
2e yz =
= 0.
+
y
z
(3)
.
p
pn
pn
u x = x + j1 ( y , z ) , u y = y + j 2 (x , z ) , u z = z + j 3 ( x, y ) .
E
E
E
:
j1 ( y , z ) j 2 ( x, z )
+
= 0,
y
x
j1 ( y , z ) j3 ( x, y )
+
(4)
= 0,
z
x
j 2 ( x, z ) j3 (x , y )
+
= 0.
z
y
,
j
j
j
j1
j
j 2
= - 2 = a (z ) , 1 = - 3 = b( y ) ,
= - 3 = g(x ) ,
y
z
x
z
x
y
a, b, g - .

j1 = a( z ) y + f1 (z ) = b( y )z + g1 ( y ) ,
j 2 = - a( z )x + f 2 (z ) = g (x )z + g 2 ( x ) ,
j3 = - b( y )x + f 3 ( y ) = - g (x ) y + g 3 (x ) ,

f i , g i - .
,
j1 = k1 zy + k 2 z + k3 y + k 4 ,
e xx =

.. . .2. /.: , 1984. 560 .

22

j 2 = m1 zx + m2 z + m3 x + m4 ,
j3 = l1 xy + l 2 x + l3 y + l 4 ,
k i , mi , li - , (4)

k1 z + k3 + m1 z + m3 = 0 ,
k1 y + k 2 + l1 y + l 2 = 0 ,
m1 x + m2 + l1 x + l3 = 0 ,
x , y . z .

k1 = - m1; k k = -l1; m1 = -l1 ,
, k1 = m1 = l1 = 0 .

k 3 = -m3 = - a3 ;
k 2 = -l 2 = a2 ;
m2 = -l3 = - a1 ,
.

j1 = a 2 z - a3 y + k 4 ,
j 2 = - a1 z + a3 x + m4 ,
j3 = - a 2 x + a1 y + l 4 .

r = xi + yj + zk , r = a1i + a2 j + a3k
j 0 = k 4 i + m4 j + l 4 k ,
,
u = j = j1i + j 2 j + j 3k = j 0 + a r
a1 , a 2 , a3
.
,
, ,

.
,

, .., x = 0, y = 0, z = 0
u x = 0, u y = 0, u z = 0

u y u x
u
u z u y
u
(5)
= 0 , x - z = 0,
= 0,
y
z
z
x
y
x

23

p
pn
pn
x , uy = y , uz = z.
(6)
E
E
E
,
. (6) ,
; ,
u y , u z
().
ux =

2. .
r l ,

. ,
. 2. , e ij = 0 ,

F = gi s n = 0 , A , .
.


s xx
= -rg ,
x

s xx = -rgx + j( y , z ) ,
(7)
j( y, z ) - ,

. 2.

. s = 0 x = 0 ,
xx

j( y, z ) = 0 .

(7)
s yy = s zz = s xz = s zy = s xy = 0

, .
, .. ,
G
s xx = rgl = ,
S
S - , G = rglS - .

s
ns
ns
rgx
nrgx
nrgx
e xx = xx = , e yy = - xx =
, e zz = - xx =
,
(8)
E
E
E
E
E
E
e xy = e zy = e xz = 0 .
, ,
.

24

u x
rgx u y nrgx u z nrgx
=,
,
=
,
=
x
E
E
z
E
y
u x u y u x u z u y u z
+
=
+
=
= 0.
(9)
+
z
x
y
x
y
z
(9)
nrgxy
nrgxz
rgx 2
ux = + y 2 ( x, z ) , u z =
+ y 3 ( y, x )
+ y1 ( y , z ) , u y =
(10)
2E
E
E
(10) (9),

y1 nrgy y 2
+
+
= 0,
E
y
x
nrgy y 3 y1
= 0,
+
+
E
x
z
y 2 y 3
+
= 0.
z
y

nrg 2
j1 = y1 +
y + z2 ,
2E
j 2 = y 2 , j3 = y 3 ,

ji . ,

rg 2
ux = x + n y 2 + z 2 + a 2 z - a3 y + k 4 ,
2E
nrgxy
uy =
- a1 z + a3 x + m4 ,
2E
nrgxz
uz =
- a 2 x + a1 y + l 4 .
2E
, , .. x = -l , y = 0, z = 0 ,
(5),
rg 2
a1 = a 2 = a3 = m4 = l 4 = 0, k 4 =
l .
2E
,
rg 2 2
ux = x - l + n y2 + z2 ,
(11)
2E
nrgxy
nrgxz
uy =
, uz =
.
2E
2E
,
. , x=0,

))

((

) (

))

25

.
x = x0
rg
x = x + u x = x0 x0 2 - l 2 + n y 2 + z 2 ,
2E
.. .
s11 .

s11 (x = -l ) = rgl .
3. ,
. 3.

x
d
, ,
F
F
uz
s xz = .
S

j
z;
d
.
z

ux = u y = 0 ,
. 3.

((

) (

))

u z = x tgj xj
:
u 1 u z 1
1 u
j
e xz = z + x =
= tgj .
z 2 x
2 x
2
2

, :
1
1 F
e xz =
s xz =
2m
2m S
:
d
tg (2j ) 2j ,
d

Fd
m =G=2
Sd

(12)

4. .
, - r
(. 4), -
f = - gr R
,
,
,
:

26

uq = uj = 0, ur = u (r ) .
r

(
R
)
:
r
r
d 1 d 2
r u = A ,
(13)

R
dr r 2 dr

. 4.
(1 + n )(1 - 2n ) .

A = rg
E (1 - n )

( )

u (0) < ;
srr (R ) = 0 .
(13)

( )

r3
r C
u (r ) = A
+ C1 + 22
10 R
3 r

(14)

C2 = 0 .
,
:

srr =

E
(1 - n )e rr + n eqq + ejj
(1 + n )(1 - 2n )

)]

(15)

(. )

e rr =

u r
u
u
, e qq = r , e jj = r
r
r
r

(16)

(14):

ur 3 Ar 2 C1
=
+ ,
err =
3
r 10 R
ur
r 2 C1
eqq = ejj =
=A
+ .
r
10 R 3

r = R .

C1 = :

3
3-n
AR
.
10
1+ n

(15)

27
2
AR 3 - n r
- ,
u (r ) = r
10 1 + n R

2
AR r 3 - n
err =
(17)
,
3 10 R 1 + n

2
AR r 3 - n
e qq = e jj =
,
10 R 1 + n

,
, e rr = 0
(17)
, ,
. :

)
s qq = (l + 2m )e qq + l (e rr + e jj ) ,

s rr = (l + 2m )e rr + l e qq + e jj ,

(18)

s jj = (l + 2m )e jj + l (e rr + e qq ) .
, .1.3,
(1 - n )E .
l + 2m =
(1 - 2n )(1 + n )

s rr =

(19)

)]

E
(1 - n )e rr + n e qq + ejj .
(1 - 2n )(1 + n )

s rr

E (3 - n ) AR r
=
- 1 .
(1 - 2n )(1 + n ) 10 R

s rr

E (3 - n ) AR 1 + 3n r
=
1
.


(1 - 2n )(1 + n ) 10 3 - n R

5. ,
p. ,
.

28


z,
R1
(. 5). ,

. ,
R2

p
. .

. 5. :

d 1 d
(20)
(ru ) = 0,


dr r dr

-
s rr (R1 ) = - p , s rr (R2 ) = 0

(21)

1
1
u (r ) = C1r + C 2 .
2
r
,
e rr =

u r 1
1
= C1 - C 2 2 ,
2
r
r

e jj =

ur 1
1
= C1 + C 2 2 ,
2
r
r

(22)

e zz = 0 .

(22)
E
(1 - n )e rr + n e zz + e jj ,
(23)
s rr =
(1 + n )(1 - 2n )

C2
E
C1
s rr =
1
2
n
(
)
.
(1 + n )(1 - 2n ) 2
r2
,

C1
C
E
(24)
- (1 - 2n ) 22 = - p ,
(1 + n )(1 - 2n ) 2
R1
C1
C
- (1 - 2n ) 22 = 0 ,
2
R2

)]

, ,
, .
,

29

R12
p
C1 = 2 (1 + n )(1 - 2n ) 2
,
E
R2 - R12
C2 =

2 2
p
(1 + n ) R21 R2 2 .
E
R2 - R1

R12
R22
p
u (r ) = (1 + n ) 2
.
(1 - 2n )r +
E
r
R2 - R12
,

R22
(1 - 2n ) - 2 ,
r

R12
R22
p
(
)
(
)
(
)
r
1
1
2
e jj =
+n 2
- n + 2 .
2
E
R2 - R1
r
R12
p
e rr (r ) = (1 + n ) 2
E
R2 - R12

(23)

R22
1- 2 .
2
2
R2 - R1 r

pR12 R22
E
(1 - n )e jj + ne rr 2 2 1 + 2 ,
s jj =
(1 + n )(1 - 2n )
R2 - R1 r
s rr (r ) =

pR12

s zz

2 pnR12
E
=
n e +e

.
(1 + n )(1 - 2n ) rr jj R22 - R12

6. ,
. .
, .
- r
f = w2r
,
r .
z

:
w
(
)(
)
d 1 d
1
1
2
+
n
n

(ru ) = -rw2r
(25)

dr r dr
E (1 - n )

r
:
R
u (0) < ;
srr (R ) = 0 .
(25) :
. 6.

30

r 3 (1 + n )(1 - 2n ) C1
C
u (r ) = -rw
+ r+ 2 .
2
8
E (1 - n )
r
2=0. 1,
.
2
u r
2 3r (1 + n )(1 - 2n ) C1
e rr =
= -rw
+ ,
r
2
8
E (1 - n )
2

ur
r 2 (1 + n )(1 - 2n ) C1
= -rw 2
+ ,
2
8
r
E (1 - n )
e zz = 0 ,
(23):
2
C1

E
2 r (1 + n )(1 - 2n )
(3 - 2n ) .
s rr =
- rw
(1 + n )(1 - 2n ) 2
8
E (1 - n )

, 1
e jj =

(26)

R 2 (1 + n )(1 - 2n )
C1 = rw
(3 - 2n ) .
4
E (1 - n )
2

u(r ) = rw2

(1 + n )(1 - 2n ) r [(3 - 2n )R 2 - r 2 ].
8E (1 - n )

(27)

(1 + n )(1 - 2n ) [(3 - 2n )R 2 - 3r 2 ],
8E (1 - n )
(1 + n )(1 - 2n ) [(3 - 2n )R 2 - r 2 ]
e jj (r ) = rw 2
8E (1 - n )

e rr (r ) = rw 2

s rr (r ) =
s jj

s zz

rw2
(3 - 2n ) R 2 - r 2 ,
8(1 - n )

rw 2
=
8

2 1+ n 2
3
2
n
R
r ,
(
)

1 - n
rw2 n
(3 - 2n )R 2 - 2r 2 .
=
4 1- n

2.2.

-
,

31


: T = T (x ) Ck = Ck (x ) , w = w( x ) (. 7).
,

s zz = s yy = s( x ) ,

s xx = s xy = s xz = s yz = 0 .

.

(17)
(
1.4)

. 7.

:
d 2e
(28)
= 0 , e zz = e yy = e( x ) .
dx 2
(28)
e = C1 x + C 2 .
(29)
-
s = 2me + [l (2e + e xx ) - Kw] ,
0 = 2me xx + [l (2e + e xx ) - Kw].

1
[Kw - 2le ] 1 1 + n w - 2n e .
e xx =
l + 2m
31- n
1- n
,
E
w
s=
e - .
1- n
3

w E
E
(C1x + C2 ) .
s=+
3 1- n 1- n

:
h

s(x)dx = 0 , s(x )xdx = 0


0

(30)

s
yz , h - .
(30)

h

w E
E
E
dx + C1
xdx + C 2
dx = 0 ,
3 1- n
1- n
1- n
0

32
h

w E
E 2
E
xdx + C1
x dx + C2
xdx = 0
3 1- n
1- n
1- n

, ,
, ,
h

w
h2
dx + C1
+ C2 h = 0 ,
3
2

w
h3
h2
xdx + C1
C
+ 2
= 0.
3
3
2

.
,


- N + C1b + C 2 a = 0 ,
- M + C1g + C 2b = 0 ,

N=

E
E
1
1
w
dx , M =
wx
dx ,
3
1- n
3
1- n
0

a=

E
E
E 2
dx , b =
xdx , g =
x dx .
1- n
1- n
1- n
0


Nb - Ma
Ng - Mb
C1 = 2
, C2 = .
b - ga
b 2 - ga
, ,
, .

2.3.

(. 8). ..
T = T (r ) - .
.
,
, ..
s zz = 0 . ,

r, q
. 8.

33

. ,

du
u
(31)
e rr =
, e qq = , e rq = e rz = e qz = 0 .
dr
r
-
s rr = 2me rr + le kk - Kw ,
s qq = 2me qq + le kk - Kw ,
0 = 2me zz + le kk - Kw ,

w = 3a T (T - T0 ) .

l
K
(32)
(e + e ) .
e zz =
w(l + 2m ) (l + 2m ) qq rr
,

s rr =

4m(l + m )
2ml
2mK
e rr +
e qq w,
(l + 2m )
(l + 2m )
(l + 2m )

4m(l + m )
2ml
2mK
e qq +
e rr w,
(l + 2m )
(l + 2m )
(l + 2m )


E
[e + ne qq ] - E w ,
s rr =
2 rr
3(1 - n )
1- n
E
E
[
]
(33)
s qq =
e
+
ne
w.
qq
rr
2
3
1
(
n
)
1- n

s qq =

ds rr s rr - s qq
+
= 0.
dr
r

(34)

(31), (32), (34)


d 2 u 1 du u 1 + n dw
+
=
3 dr
dr 2 r dr r 2

d 1 d
1 + n dw
ru
(
)
= 3 dr .
dr r dr

1 d
(ru ) = 1 + n w + C1 .
r dr
3

(35)

34

u=

1+ n
3r

R1

w(r )rdr +

C1
C
r+ 2 ,
r
2

(36)

R1 - .

.
,
.

. ,
.
.
, ,
,
. ,
:
, .
,
( , , ,
.). , ,
,
(.
1, 1.8-1.10). ,
.
2.4.
.
,
.
. T = T (r ) . ,
, , ,
,
, q
. , (31).
z ,
,
e zz = const .

.
.
, -
s rr = (l + 2m )e rr + l (e qq + e zz ) - Kw ,
s qq = (l + 2m )e qq + l (e rr + e zz ) - Kw ,

35

s zz = (l + 2m )e zz + l(e qq + e rr ) - Kw ,
s rq = s rz = s qz = 0 .

( E , n ) (19),
nE
E
(1 - n )E du +
u

s rr =
w,
+ e zz 3
1
2
(1 - 2n )(1 + n ) dr (1 - 2n )(1 + n ) r
(
n
)

nE
(1 - n )E u +
E
du

s qq =
(37)
w,
+ e zz (1 - 2n )(1 + n ) r (1 - 2n )(1 + n ) dr
3(1 - 2n )
nE
E
(1 - n )E e +
u du
s zz =
w.
+ zz
(1 - 2n )(1 + n )
(1 - 2n )(1 + n ) r dr 3(1 - 2n )
(37) (34),

d 2 u 1 du u 1 1 + n dw
+
=
dr 2 r dr r 2 3 1 - n dr

d 1 d
1 1 + n dw
(38)
(
ru
)
= 3 1 - n dr
dr r dr
(35) .
,

1 1+ n 1
u=
3 1- n r

R1

w(r )rdr +

C1
C
r+ 2 .
2
r

(39)



(. 9):
r = R1 : s rr = 0 ;
(40)
r = R2 : s rr = 0

R1
:
R2
R2
(41)
s zz (r )rdr = 0

R1

. 9.


.
,
.

36

,
C1 , C 2 , e zz .
(31)
r

1 1+ n
1
C C
e rr =
w(r ) - 2 w(r )rdr + 1 - 22 ,
(42)

2 r
3 1- n
r

R1

e qq =
,

11+ n 1
31- n r2

s rr

s qq

R1

E
1
=3(1 - n ) r 2

1
E
=
3(1 - n ) r 2

C1 C 2
+ 2 .
2
r

w (r )rdr +

w(r )rdr + A -

R1

(37)

w(r )rdr -

R1

B
r2

E w
B
+ A+ 2 ,
1- n 3
r

(43)

C2 E
E
C1

+
ne
,
=
B
.
(44)
zz
(1 - 2n )(1 + n ) 2
1+ n


E
nE
(1 - n )E e =
w+
C1 +
s zz = (1 - 2n )(1 + n )
(1 - 2n )(1 + n ) zz
3(1 - n )
.
(45)
E
=w + 2 An - Ee zz .
3(1 - n )
(40),
A B
B
A - 2 = 0,
R1

A=

E
1
3(1 - n ) R2 2

R2

w(r )rdr + A -

R1

B
R2

= 0,

, (,

, ) .

e zz = 0 .

37

B=

R12 E

3(1 - n ) R2 2 - R12

A=

R2

w(r )rdr ,

R1
R2

E
1
3(1 - n ) R2 2 - R12

w(r )rdr .

(46)

R1

, (44)
1 1+ n
(1 - 2n )wcp - 2ne zz ,
C1 =
3 1- n
R2 1+ n
C2 = 1
wcp ,
6 1- n

wcp =

2
R22 - R12

R2

rw(r )dr -

(47)

R1

w (
) .
, ,
,
R2

R1

E
- 3(1 - n ) w + 2 An - Ee zz rdr = 0

E
wcp + 2 An - Ee zz = 0 ,
3(1 - n )
(46), (47)
e zz = - wcp .
-

(48)

2.5.
,
,
, T = T (r ) C k = C k (r ) .
. ,
s qr = s qj = s jr = 0 ,
(49)

e qr = e qj = e jr = 0 ,

(, , ,
).

38

du
u
(50)
, e qq = e jj = .
dr
r

s rr 2s rr - s qq - s jj
(51)
+
=0
r
r
(50) ,
E , n , ,

nE
E du
u
E
du
s rr =
+
w,
+2 1 + n dr (1 + n )(1 - 2n ) dr
r 3(1 - 2n )
nE
E u
u
E
du
s qq = s jj =
+
(52)
w.
+2 1 + n r (1 + n )(1 - 2n ) dr
r 3(1 - 2n )
(52) (51),

d 2u
1 du u 1 1 + n dw
+
2
r dr - 2 = 3 1 - n dr
2

dr
r

d 1 d r 2 u 1 1 + n dw
.
(53)

=
dr r 2 dr 3 1 - n dr

1 d r 2u 1 1 + n
w + C1 .
=
3 1- n
r 2 dr

e rr =

( )

( )

1 1+ n 1
u=
3 1- n r 2

w(r )r 2 dr +

R1

C1
C
r + 22 ,
3
r

(54)

R1 - .
,

e rr

2 1+ n 1
=3 1- n r3
e qq = e jj =

w(r )r 2 dr +

R1

1 1+ n 1
3 1- n r3

1 1+ n
C
C
w + 1 - 2 32 ,
3 1- n
3
r

w(r )r 2 dr +

R1

C1 C 2
.
+
3 r3

, (52)

s rr

2 E 1
=3 1- n r 3

R1

w(r )r 2 dr +

1 E
C E
C1 - 2 32
.
3 1 - 2n
1
+
n
r

(55)

39


. ,
, .. (40).
C1 C 2 ,

C1 =

1 - 2n
2
1 - n R23 - R13

C2 =

1 1+ n
3 1- n

R2

w(r )r 2 dr ,

R1

R13
R23 - R13

R2

w(r )r 2 dr .

(56)

R1

R1 0 , .. ,

C1 =

s rr = -

1 - 2n 2
1 - n R23

2 E 1
3 1- n r3

1 1+ n 1
u=
3 1- n r 2

R2

w(r )r 2 dr , C 2 = 0 ,

w(r )r 2 dr +

2 E 2
3 1 - n R23

2 1 - 2n 1
w(r )r 2 dr + r
3 1 - n R23

R2

R2

w(r )r 2 dr ,

(57)

w(r )r 2 dr .

,
, ,

1
2
lim
w(r )r dr = lim w(r )r = 0 .
r 0 r 2
r 0
0

2.6.
2.6.1.
-
, h1 h2 .
1 2.
,
,
,
, . ,
.
e xx = e xx ( x ) , e yy = e zz = e( x ) ,

40

s yy = s zz = s( x ) .
(29),
, 1 2,
0 h = h2 + h1 .

e = Ax + B ,
w E
E
( Ax + B ) ,
s= +
(58)
3 1- n 1- n
11+ n
2n
e xx =
we,
3 1- n
1- n

Nb - Ma
Ng - Mb
A= 2
, B=- 2
,
b - ga
b - ga
h1

N=

E
1
1
w1 ( x ) 1 dx +
3
1 - n1
3

h1 + h2

0
h1

M =

w2 ( x )

h1
h1 + h2

E
1
1
w1 ( x )x 1 dx +
3
1 - n1
3
0

h1

a=

E1
dx +
1 - n1

h1 + h2

g=

h1

E2
dx , b =
1 - n2

E1 2
x dx +
1 - n1

h1
h1

h1

w2 (x )x

(59)

E2
dx ,
1- n2

E1
xdx +
1 - n1

0
h1 + h2

h1

E2
dx ,
1- n2

h1 + h2

h1

E2
xdx ,
1- n2

(60)

E2 2
x dx .
1- n2

,
a, b, g
.
.
2.6.2.
-
,

, .
- R1 , R2 , - R . ,
, . ,

41

r = R2 u
s :
r = R2 :
u1 = u 2 , s1 = s 2 .
(61)
, ..
r = R1 : s1 = 0 ;
(62)
r = R : s2 = 0 .
(63)
,
,
u z = 0, e zz = 0 .
,

e zz = const (. 4).
.

(38),

1 1 + n1 1
3 1 - n1 r

u1 =

R1
r

1 1+ n2 1
3 1- n2 r

u2 =

w1 (r )rdr +

w(r )rdr +

R2

A1
B
r+ 1,
r
2
A2
B
r+ 2 .
r
2

(64)

(61) (63)
. ,
:
r

1 1 + ni
1
A B
w(r ) - 2 w(r )rdr + i - 2i ,
e rr ,i e i =

3 1 - ni
2 r
r

Ri

e qq,i

1 1 + ni 1
=
3 1 - ni r 2

w(r )rdr +

Ri

Ai Bi
+
,
2 r2

(65)

1 E1 1
s1 = 3 1 - n1 r 2
1 E2 1
s2 =
3 1- n2 r 2

w1 (r )rdr +

R1
r

R2

w(r )rdr +

E1
A1
E1 B1
(1 - 2n1 )(1 + n1 ) 2 (1 + n1 ) r 2

E2
A2
E 2 B2
(1 - 2n 2 )(1 + n 2 ) 2 (1 + n 2 ) r 2

(66)

42

,

E1
A1
E1 B1
= 0,
(1 - 2n1 )(1 + n1 ) 2 (1 + n1 ) R12

1 1 + n1 1
3 1 - n1 R2
1 E1 1
3 1 - n1 R2 2
=

R2

R2

w1 (r )rdr +

R1

w1 (r )rdr +

R1

A1
B
A
B
R2 + 1 = 2 R2 + 2 ,
R2
R2
2
2

E1
A1
E1
B1
=
(1 - 2n1 )(1 + n1 ) 2 (1 + n1 ) R2 2

(67)

E2
A2
E2
B2
,
(1 - 2n 2 )(1 + n 2 ) 2 (1 + n 2 ) R2 2

1 E2 1
3 1- n2 R2

w2 (r )rdr +

R2

E2
A2
E 2 B2
.
(1 - 2n 2 )(1 + n 2 ) 2 (1 + n 2 ) R 2

.

Db + Cx
Da + Cg
, A2 =
,
A1 =
gb - ax
gb - ax

A1 R12
1 1+ n2
B1 =
, B2 =
3 1- n2
2 1 - 2n1

R2

A2 R 2
w2 rdr +
,
2 1 - 2n 2

(68)

a=

g=

R12
R2
2
+
, b = R2 +
,
1 - 2n1
1 - 2n 2
E2
R22 - R12 , x =
R22 - R 2 ,
(1 - 2n 2 )(1 + n 2 )

R22

E1
(1 - 2n1 )(1 + n1 )

R2
R

(
1+ n2 )
2 (1 + n1 )

C=
w1rdr w2 rdr ,
(1 - n 2 )
3 (1 - n1 )

R1
R2
R2
R

E2
2 E1

D=-
w1rdr w2 rdr .
(1 - n 2 )
3 (1 - n1 )

R1
R2

(69)

43

,
, .
(64) (66) :

s qq,i =

Ei
1
3(1 - n i ) r 2

wi (r )rdr -

Ri

s zz ,i = -

Ei wi
Ei
Ai
Bi Ei
,
+
+
1 - n i 3 (1 - 2n i )(1 + n i ) 2 (1 + n i )r 2

Ei
n i Ei
wi (r ) +
A.
(1 - 2n i )(1 + n i ) i
3(1 - n i )

(70)

2.7.
2.7.1.

, ,
. ,
, .

**.
1. ,
. , ,
.
2. , ..
.
, ,
.
.
3.
,
.
4. ,
.

. ,
.
5. ,
.
6. ,
.
7.

,
..

, ,
, ,
**

44

..
,
.

,
-.
2.7.2.
1.

, .
, ,
, , .
2.
(, -; -, -)
.
(
).
3. ,
-
.

l= l p h + l m (1 - h) , E= E p h + Em (1 - h)

1
1
l-1= l p h + l m (1 - h) , E -1= E p -1h + Em -1 (1 - h)
4. ,
-
,
.

l = l p h + l m (1 - h) , E = E p h + Em (1 - h)

l-1 = l p -1h + l m -1(1 - h) , E -1 = E p -1h + Em -1 (1 - h)


5.

.

45

6.
(-)

.
.
7.

( )
.
8. ,
,
.
9.
, ,
.
10.
,

, .
11.
,

, .
12.

. ,
,
.
13.
,
.
;
.
14.
, ( )
, .
.

46

15*.
, ,
.

:
(. 1),
u = ux , u y , uz :

u y
u x
u
, e yy =
, e zz = z ,
x
z
y
y
1 u x u y
1 u z u y

,
+
+
=
=
e
,
e
x
xy
zy
x
z
2 y
2 y
. 1.
u
1 u
e xz = x + z ,
x
2 z
(. 2)
z

e xx =

e rz

u = ur , uj , u z :
u
u
1 uj ur
+ , e zz = z ,
e rr = r , ejj =
r
z
r j
r
uj
1 1 ur
1 uj 1 u z
1 u
u
,
+ r , ejz =
+
= z + r , e rj =
r r
2 r j
2 z r j
2 r
z
z

dz

(r ,j , z )

dr

dr

dQ

y
j

(r ,Q,j )

dj

.2.

dj

.3.

(.3), u = ur , uj , uq :

ur
,
r
1
ejj =
r sin q

e rr =

1 uq ur
+ ,
r q
r
uj ur uq ctgq
+ +
,
j
r
r

eqq =

47

1 uj
1 ur uj
1 1 ur uq uq
- ,
+
- , ejr =
+
e rq =
r
2 r r sin q j
r
r
2 r q
1 1 uq 1 uj uj ctgq
.
+
ejq =
r
2 r sin q j r q

1,
1.3 ( (14)).

s rr 1 s rq s zr s rr - s qq
+
+
+
+ Kr = 0 ,
r
r q
z
r
s rq 1 s qq s qz 2s rq
+
+
+
+ Kq = 0 ,
r
r q
z
r
s rz 1 s qz s zz s rz
+
+
+
+ Kz = 0.
r
r q
z
r

s rr
1 s rq 1 s rj 2s rr - s qq - s jj + s rj ctgj
+
+
+
+ Rr = 0 ,
r sin j q
r j
r
r
s qr
1 s qq 1 s qj 3s qr + 2s qj ctg j
+
+
+
+ Rq = 0 ,
r
r sin j q
r j
r
s jr
1 s jq 1 s jj s jj - s qq ctg j + 3s rj
+
+
+
+ Rj = 0 .
r
r sin j q
r j
r